1990
DOI: 10.1128/mcb.10.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of two mouse dilute locus deletion mutations: spontaneous dilute lethal20J and radiation-induced dilute prenatal lethal Aa2 alleles.

Abstract: The dilute (d) coat color locus of mouse chromosome 9 has been identified by more than 200 spontaneous and mutagen-induced recessive mutations. With the advent of molecular probes for this locus, the molecular lesion associated with different dilute alleles can be recognized and precisely defined. In this study, two dilute mutations, dilute-lethal20' (d'a01) and dilute prenatal lethal Aa2, have been examined. Using a dilute locus genomic probe in Southern blot analysis, we detected unique restriction fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 40 publications
(60 reference statements)
3
31
0
Order By: Relevance
“…l20J (Strobel et al, 1990;Wu et al 1997 (Wu et al, 1998). These primary cultures were prepared from the skin of newborn mice as described previously , and they were grown on gelatin-coated Labtek chamber slides with coverglass bottoms (#155380; Nalge Nunc International, Naperville, IL) or #1.5 round coverslips in Ham's F-10 medium supplemented with 10% horse serum, 2% fetal calf serum, 1% penicillin streptomycin, 0.1 M dibutryl cAMP, and 85 nM phorbol 12-myristate 13-acetate (#P-8139; Sigma-Aldrich, St. Louis, MO).…”
Section: Melanocyte Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…l20J (Strobel et al, 1990;Wu et al 1997 (Wu et al, 1998). These primary cultures were prepared from the skin of newborn mice as described previously , and they were grown on gelatin-coated Labtek chamber slides with coverglass bottoms (#155380; Nalge Nunc International, Naperville, IL) or #1.5 round coverslips in Ham's F-10 medium supplemented with 10% horse serum, 2% fetal calf serum, 1% penicillin streptomycin, 0.1 M dibutryl cAMP, and 85 nM phorbol 12-myristate 13-acetate (#P-8139; Sigma-Aldrich, St. Louis, MO).…”
Section: Melanocyte Culturesmentioning
confidence: 99%
“…To accomplish this, we microinjected primary melanocytes cultured from the skin of newborn mice homozygous for a true null allele at dilute (d l20J ) (Strobel et al, 1990;Wu et al, 1997) with plasmids encoding various full- (Figure 6, J-L), which lack both exons D and F, did not rescue a single mutant cell (n ϭ 74 and 72 for MC MV⌬F and BR MV, respectively) (given that the fluorescence signal from these GFP-tagged myosins, in contrast to the signal from the GFP-tagged dominant negative constructs, was often very weak, the melanocytes in these experiments were coinjected with plasmid EGFP C1, which allowed for unequivocal identification of all microinjected cells, and, therefore, accurate scoring of rescue; the fluorescence images in C, F, I, and L reveal primarily the distribution of the unfused GFP expressed from this plasmid). Furthermore, in dilute melanocytes that were injected with just the plasmids encoding GFP-tagged myosin Va isoforms, and that happened to exhibit a strong fluorescence signal, myosin MC MV (Figure 7, A1-B2) and MC MV⌬D (Figure 7, C and D, plus inset) showed extensive colocalization with black, end-stage organelles in rescued cells, whereas MC MV⌬F ( Figure 7, E and F) and BR MV (Figure 7,G and H) showed no tendency to associate with the melanosomes clustered in the perinuclear region.…”
Section: Full-length Myosin Va Also Requires Exon F To Colocalize Witmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be reduced to one-half if one assumes that nearly one-half of the induced deletions were too small to be detectable with the array-CGH method. However, the difference cannot be further reduced by assuming that small mutations were the predominant-type of deletions, because many mutagenesis studies in cultured mammalian cells at the HPRT gene [e.g., see (39)] and also in germ cells of mice [e.g., see (5,40,41)] have consistently indicated that large deletions are the predominant type of mutations induced by radiation.…”
Section: Results Of Array-cgh Studiesmentioning
confidence: 99%
“…However, one mutant allele (d l20J ) at the d locus (one of the specific locus genes used in the SLT), which was known to cause homozygous lethality, was found to be an intralocus deletion (41); also, an artificially knocked-out null allele of the s gene (another gene used for SLT studies) caused homozygous lethality (46). These results raised the question of why the mutant homozygous animals used for the tester strain were viable and fertile.…”
Section: Likelihood Of Hypothesismentioning
confidence: 99%